TESTING THE CHARACTERISTICS OF FREE AND FORCED OSCILLATIONS ON FAP 2228 OFF-ROAD VEHICLE - Mićović, Aleksandar M (Journal of Applied Engineering Science, 2013)
The paper presents the testing of free and forced oscillations characteristics on FAP 2228 BS/A-45 off-road vehicle. The testing of free oscillations was conducted according to SORS 9127 (Standard of Defence of the Republic of Serbia) in laboratory conditions. The testing of forced oscillations was conducted in the course of driving on various surface paths - the heath in Deliblatska pescara, gravel at the territory of Fruska gora, on concrete surface at the runway of the Kovin airport, as well as on the asphalt surface of Belgrade-Šid highway. The testing was carried out according to SORS 0318 and ISO 2631 standards, and the results were evaluated according to 2002/44/EC Directive. U radu je dat prikaz ispitivanja karakteristika sopstvenih i prinudnih oscilacija terenskog vozila FAP 2228 BS/A-45. Ispitivanje sopstvenih oscilacija vozila obavljeno je prema SORS 9127 u laboratorijskim uslovima. Ispitivanje prinudnih oscilacija vozila obavljeno je vožnjom po stazi - ispresecana ledina, u oblasti Deliblatske peščare, ravničarski makadam u oblasti Fruške gore, po betonskoj podlozi na pisti aerodroma Kovin, kao i po afaltnoj podlozi autoputa Bgd - Šid. Ispitivanja su obavljena prema SORS 0318 i ISO 2631, a rezultati su ocenjeni prema direktivi 2002/44/EC.